The Effect of Part-time Work, Work Stress, Learning Environment, Learning Motivation and on Academic Achievement of Student Employees in Management Study Program (Empirical Study at Pembangunan Panca Budi University) - Hidayatin, Rahmadani (Journal of Community Research and Service, 2023)
This research was conducted on Employee Students of the Management Study Program at Pembangunan Panca Budi University, Medan. The research objective is to identify and analyze the effect of part-time work, work stress, learning environment and learning motivation on academic achievement. The population in this study was 431 respondents who were Friday and Saturday Employee Class Students for the period 2020 to 2022. The number of samples taken in this study were 82 respondents. The sample size is determined by the Slovin formula with an error tolerance of 10%. This study uses quantitative data processed with the SPSS application with multiple linear regression analysis models. The data source used is primary data taken directly from the respondents. The results showed that part-time work, work stress and learning motivation had a positive and significant effect on academic achievement. While the Learning Environment has no effect and is not significant on Academic Achievement. Simultaneously Parttime Work, Work Stress, Learning Environment and Learning Motivation have a positive and significant effect on Academic Achievement. The magnitude of the influence contribution of all variables is 31.0% and the rest is influenced by other variables not examined in this study.